Islamic banking : how to manage risk and improve profitability - El Tiby, Amr Mohamed, 1956- (Hoboken, N.J. : Wiley, 2011)
'Islamic Banking will be about the nature of risk in Islamic banking and the regulatory framework which includes capital adequacy, corporate governance, transparency and risk associated with Islamic banking. The book will cover materials about Islamic banking and also will show how each of these issues defers from the non-Islamic Banking, shading light on the effect of the global economic crisis on Islamic banks vs. conventional banks. It will discuss history and development, the nature of risk, the importance and role of capital, corporate governance and transparency, the salient features of Islamic banking that distinguishes it from non-Islamic banking, and the development of the regulatory bodies and supervisory agencies that support the Islamic banking system. The book will try to give answers to questions such as: Is the existing regulatory framework sufficient enough to - Ensure safe and sound banking system? Face the inherent risk associated with Islamic banking? Prevent systemic risk in the banking system? The book concludes with discussions on (1) the relationship between the Islamic banking regulators and the western regulators, and (2) the obstacle and challenges from regulatory prospective that faces the Islamic banking'--
Islamic Banking; Contents; List of Tables; Foreword; Preface; Acknowledgments; Introduction; PART ONE Understanding the Origins; CHAPTER 1 Introduction to Islamic Banking; CHAPTER 2 History and Development of Islamic Banking; PART TWO Risk in Islamic Banking; CHAPTER 3 The Nature of Risk in Islamic Banking; CHAPTER 4 The Inherent Risk in Islamic Banking Instruments; CHAPTER 5 Operational Risk in Islamic Banking; CHAPTER 6 The Islamic Capital Market; PART THREE Capital Adequacy; CHAPTER 7 The Importance and Role of Capital-Literature Review.
Includes bibliographical references and index.
Print version record.
Keywords: Banks and banking -- Islamic countries; Risk -- Islamic countries; Banks and banking -- Islamic countries; Risk -- Islamic countries; Business; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Risk; Islamic countries; Electronic books